RKM Planning and Management System in the Regional Government of Magelang City: Proposed Concept - Fadhilah, Alfira Nisa; Primadewi, Ardhin (Universitas Muhammadiyah Yogyakarta, 2024)
Magelang City is one of the cities in Central Java province which has many community needs that must be managed properly. The problem of community needs plan (RKM) is important to consider, because it will affect the quality of life of the community. The Regional Development Planning Agency (Bappeda) is the government agency at the regional level responsible for formulating regional development plans and strategies. In Magelang City, Bappeda of Magelang City has a very important role in taking care of the community needs of each Neighborhood Association (RT). Bappeda of Magelang City has a role in taking care of the community needs of each RT in the city of Magelang such as regional development plans that cover the needs of the people of each RT, facilitating development planning meetings and so on. The current system is still an online repository in managing the budget. Inappropriate budget planning can be the cause of an imbalance between needs and budget allocations in community empowerment. Overcoming these difficulties, Bappeda of Magelang City needs to carry out good budget planning and management. In accordance with applicable regulations and standards, and equipped with strict monitoring and evaluation. Therefore, a community needs planning system is needed that can identify and meet community needs properly. This system is intended for the Bappeda of Magelang City in activity management, and RT in planning activities according to the needs of the community. This system will be delivered to each of the neighbourhoods in the city of Magelang every year. This will ensure effective and efficient activity management, which in turn can provide benefits for regional development and the people of Magelang City. This research was conducted using the Ward and Peppard method with Value Chain Analysis and Critical Success Factors (CSFs). The output generated from this research is in the form of strategy recommendations from the results of Bappeda internal and external environmental analysis, as well as proposed information systems that can improve the quality of a more optimal system.